The Mediating Effect of Strategic Agility in the Relationship of Supply Chain Management Activities and Firm Performance of the Textile Industry of Indonesia - Suradi Suradi; Mahrinasari MS; Sri Hasnawati (International Journal of Supply Chain Management, 2020)
The study purpose is to investigate the mediating effect of strategic agility in the relationship of supply chain management activities (SCMA) and firm performance (FP) of the textile industry of Indonesia. For this purpose, data was collected from 300 supply chain managers by using a simple random sampling technique which yield a 50 percent response rate. The Structural Equation Modeling (SEM) has applied for the hypothesis testing. The direct effect of the study has shown that SMA has positive and significant relationship with the strategic agility (SA) and FP which supports to the hypothesis. In addition, SA also has also an association with the FP. On the other hand, the indirect mediating effect also show that SA is partially mediates in the relationship of SCMA and FP in the textile industry of Indonesia. Therefore, this mediating effect is considered to be a big contribution of the study which could become a new research area in future. The research limitations and future directions are discussed at the end of the study.